Legal Status Of Land Rights Due To Natural Disasters In The National Agrarian Legal System - Mustaqim; Mustika Mega Wijaya (UNIVERSITAS PAKUAN, 2026)
Natural disasters are events that not only have an impact on the humanitarian aspect, but also raise agrarian law issues, especially related to the legal status of land rights. Changes in the physical condition of the land due to natural disasters, such as abrasion, landslides, and tsunamis, have the potential to eliminate the object of land rights and create legal uncertainty for rights holders. This article aims to analyze the regulation of the legal status of land rights due to natural disasters in the national agrarian legal system, its juridical implications on the sustainability and abolition of land rights, and the concept of legal protection and certainty for rights holders from the perspective of agrarian justice. The research method used is normative legal research with a legislative and conceptual approach. The results of the study show that the regulation of land destroyed by natural disasters in the national agrarian law is still implicit and does not provide adequate legal certainty. Natural disasters do not necessarily remove land rights, but rather require clear administrative determinations. The State, within the framework of the Right to Control the State, has a constitutional obligation to provide substantive legal protection to disaster victims through compensation, relocation, or the granting of replacement land. Therefore, responsive and fair agrarian law reform is needed to ensure legal certainty and protection of land rights for communities affected by natural disasters.Keywords: Land Rights, Natural Disasters, Destroyed Land, Legal Certainty, Agrarian Justice.